A Robust Protocol for CRISPR‐Cas9 Gene Editing in Human Suspension Cell Lines. Issue 11 (8th November 2021) - Wardyn, Joanna D.; Chan, Allison S. Y.; Jeyasekharan, Anand D.
Abstract: The implementation of clustered regularly interspaced short palindromic repeats (CRISPR)‐Cas9 systems in mammalian cells has sparked an exciting new era in targeted gene editing. CRISPR‐Cas9 technologies allow gene function to be interrogated by gene deletions, mutations, and truncations, and by epitope tagging and promoter activity modulation. Many robust protocols have been published to date on CRISPR‐Cas9 techniques, however, most of these focus on adherent cell lines. Suspension cell lines, typically of hematolymphoid origin, such as Jurkat, Daudi, and TOLEDO, pose unique challenges to the setup of CRISPR experiments. Here, using B cell lymphoma cells as a primary model, we describe a comprehensive protocol for targeted gene manipulations using the CRISPR‐Cas9 system in suspension cells. We also highlight necessary optimization steps to make this approach universal to other suspension cell lines. We first describe a detailed protocol for transient expression of the Cas9 nuclease and guide RNAs. We then suggest workflows for obtaining single‐cell clones and for screening for successful homozygous knockout (KO) clones in suspension lines. This protocol aims to serve as a comprehensive resource to facilitate gene editing experiments for users starting CRISPR‐Cas9 gene editing protocols on suspension cell lines or those looking to optimize their current workflows. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Transient CRISPR Cas9‐gRNA delivery for gene knockout by Neon TM electroporation Support Protocol 1 : Designing and preparing gene‐specific gRNA Support Protocol 2 : Preparation of conditioned medium and culture vessels for single‐cell FACS Alternate Protocol 1 : Transient CRISPR Cas9‐gRNA delivery for gene knockout by Nepagene electroporator Basic Protocol 2 : FACS and single‐cell clone generation Alternate Protocol 2 : Manual cell dilution to obtain single‐cell clones Basic Protocol 3 : Confirming indels status in single‐cell clones by PCR on genomic DNA and Sanger sequencing